Temas de mitología pagana en iglesias cristianas de Oriente - Blázquez Martínez, José María (Antigüedad y Cristianismo, 1990)
The utilization by the Christians of scenes taked from the classical mythology is proved in the mosaics of various churches not only in the Eastern Empire but also in the Western. Especially the Dionisiac themes, such as the recollection and the trampling of the grapes by foot, passed on to the christian symbology due to the resurrection character allusive to the Eucharist. Other pagan scenes adopted by the Christians were the Triumph of Dionisius, the Works of Hercules and the Legend of Hipolytus. All of which demonstrate that the Christian artists had a grand knowledge of the classical mythology.